A nitrogén stabilizátor és lombtrágya együttes alkalmazásának hatékonysága a kukorica egészségi állapotára - Rácz , Dalma Emese; Radócz , László (GEORGIKON FOR AGRICULTURE, 2020)
It is known that the utilization of the applied nitrogen-based fertilizers due to nitrate leaching, denitrification and ammonia evaporation is far from complete, therefore, the application of nitrogen stabilizers is becoming a sensible solution, which also leads to higher yield production through the reduction of nitrogen losses. In this experiment, the combined effect of the nitrapyrin (nitrogen stabilizer) and foliar fertilizer was investigated on the health of corn. The efficiency of treatments was monitored by measuring the nitrate-content in the soil, biomass production (root mass, stem thickness), chlorophyll-content, the length and diameter of corncobs, thousand kernel weight. Furthermore, the changes in the quality parameters of the yield (protein, oil and starch content) was also measured. In all parameters, significant difference was observed between the treated and untreated field.
Keywords: nitrogen stabilizer; nitrapyrin; foliar fertilizer; micronutrients; plant protection